The Correlation of Body Mass Index, Socio-Economic Status, and Motivation With Physical Activity at Productive Age at 'Aisyiyah Yogyakarta University - Annisa Syahnaz Najiha; Indriani Indriani; Veni Fatmawati (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
The lack of physical activity was one of the causes of several health problems and deaths whose prevalence was increasing throughout the world. University was a gathering place for all university members including students, lecturers and teaching staff who were at risk of low physical activity and other lifestyle behaviors. Penelitian ini bertujuan untuk mengetahui hubungan indeks massa tubuh (IMT), status sosial ekonomi dan motivasi terhadap aktivitas fisik pada usia produktif di Universitas ‘Aisyiyah Yogyakarta. A cross-sectional method was used, and a random sampling technique was taken. The sample was 380 respondents with an age range of 20-59 years. Data analysis used the chi square test to determine the relationship between physical activity and its determinants and logistic regression to determine the predictors of physical activity. Based on 380 respondents, 47.2% were in the inactive category with an average of Metabolic Equivalent Task (METs)= 402.56 ± 121,140 and duration = 88.67 ± 59,600 per minute per week. There was a significant correlation between age, occupation, body mass index (BMI), motivation, availability of sports facilities with physical activity. Based on multivariate analysis, it was found that BMI, age and motivation had an influence on physical activity. The level of physical activity among university members was still low and there was a need for university strategies to increase knowledge and behavior to become an active campus with healthy campus campaigns, organizing health checks, championships between campus sports clubs and other strategies.